2020
DOI: 10.18632/aging.103379
|View full text |Cite
|
Sign up to set email alerts
|

MiR-126 promotes esophageal squamous cell carcinoma via inhibition of apoptosis and autophagy

Abstract: MiRNA-126 (miR-126) has been shown to be involved in various malignancies as well as other biological processes. However, currently, its role in esophageal squamous cell carcinoma (ESCC) is not well understood. The present study is focused on the mechanisms that underlie the effect of miR-126 on cell survival and death (apoptosis and autophagy) in ESCC cells. MiR-126 expression was found to be enhanced in ESCC cells and tissues. Downregulation of miR-126 suppressed cell survival, and TUNEL staining indicated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…In ESCC, multiple micro-RNAs have been found to play important roles. For example, miR-126 promotes ESCC progression through inhibiting autophagy, and miR-4306 inhibits ESCC cell proliferation via SIX3 [11,12]. As an important member of microRNA family, miR-18a-5p takes part in the progression of various cancers, such as head and neck squamous cell carcinoma, endometrial cancer, and hepatocellular carcinoma [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…In ESCC, multiple micro-RNAs have been found to play important roles. For example, miR-126 promotes ESCC progression through inhibiting autophagy, and miR-4306 inhibits ESCC cell proliferation via SIX3 [11,12]. As an important member of microRNA family, miR-18a-5p takes part in the progression of various cancers, such as head and neck squamous cell carcinoma, endometrial cancer, and hepatocellular carcinoma [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…More and more investigations illustrated that numerous miRNAs play imperative roles in biological processes including migration, invasion, transformation, and apoptosis. For example, miR-126 inhibits apoptosis and autophagy of esophageal squamous cell carcinoma (ESCC) [31]. miR-32 accelerates ESCC progression via regulating CXXC5/TGF-β pathway [6].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, miR-126 suppressed osteosarcoma proliferation, migration, invasion, and EMT by targeting ZEB1 and inactivating the JNK and JAK1/STAT3 pathways ( 138 ). The role of miR-126 in ESCC was investigated in a study by Li et al ( 139 ), which revealed that miR-126 was upregulated in TE13 cells, Eca109 cells, and ESCC tissues, and targeted the 3'-UTR of STAT3, enhancing its transcription and translation, and thus increasing tumor cell viability. Considering its differing characteristics in other types of cancer, the specific role of miR-126 under certain conditions of EC remains to be determined.…”
Section: Regulation Of Stat3 In Ecmentioning
confidence: 99%